Permanent lesion to the corticospinal tract after therapy with capecitabine - Wagner-Altendorf, Tobias A (BMJ Case Rep, 2019)
Capecitabine is an oral fluoropyrimidine used to treat solid tumours such as colorectal and breast cancer. A rare but severe side effect is capecitabine-induced leukoencephalopathy, including bilateral lesion to the corticospinal tract. However, neurological symptoms due to capecitabine treatment are usually reported to be reversible after discontinuation of capecitabine. Here, we present the case of a patient with bilateral degeneration of the corticospinal tract and progressive spastic tetraplegia after chemotherapy with capecitabine mimicking primary lateral sclerosis. Although therapy with capecitabine was ended, symptoms substantially worsened over the following years and the patient finally died from aspiration pneumonia almost 3 years after the application of capecitabine.